2009
DOI: 10.1080/07357900802350822
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase I Glu111Ala Polymorphism in Patients with Breast Cancer

Abstract: Effect of advanced glycation end products (AGEs) in the pathogenesis of cancer could be diminished by interaction with soluble RAGE or by reducing AGE-precursors via glyoxalase I. Glu111Ala polymorphism of glyoxalase I gene, AGEs, and sRAGE serum levels were studied in 113 breast cancer patients and in 58 controls. Higher frequency of the mutated C allele was found in patients with negative estrogen receptors and in patients in clinical stage III compared to controls (P< 0.05). The presence of the C allele cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
3
16
4
Order By: Relevance
“…In contrast to our observation, Antognelli and co‐investigators demonstrated that women with Ala/Glu and Glu/Glu genotypes or carriers of Glu allele were associated with breast cancer risk suggesting a possible role of Glu allele in progression of local to advanced breast cancer 15 . Some investigators have determined the genotype and allelic frequencies of GLOI Ala111Glu polymorphism but did not examine the correlation with breast cancer risk 14 . The odds ratio noted for Ala/Glu and Glu/Glu genotypes or carriers of Glu allele in the present study were much lower than the values reported by Antognelli and co‐investigators 15 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our observation, Antognelli and co‐investigators demonstrated that women with Ala/Glu and Glu/Glu genotypes or carriers of Glu allele were associated with breast cancer risk suggesting a possible role of Glu allele in progression of local to advanced breast cancer 15 . Some investigators have determined the genotype and allelic frequencies of GLOI Ala111Glu polymorphism but did not examine the correlation with breast cancer risk 14 . The odds ratio noted for Ala/Glu and Glu/Glu genotypes or carriers of Glu allele in the present study were much lower than the values reported by Antognelli and co‐investigators 15 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, the frequencies of the genotypes and alleles were increased in breast cancers than in the controls irrespective of ethnicity. Several studies reported that Glu allele frequency in different normal populations across the world showed values between 27.2% and 51.7% 14,15,18,27–31 . Our result on Glu allele frequency in the Malay, Chinese and Indian control groups is also within the reported range.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, other groups have demonstrated that AGEs accumulate in mamma carcinoma [53] and that glyoxalase expression [54] and polymorphisms are relevant for breast cancer [55]. Consequently, targeting glyoxalase has been proposed as cancer therapy [10], [56] and even oral consumption of methylglyoxal has been investigated in mice to treat cancer [57].…”
Section: Discussionmentioning
confidence: 99%
“…We studied the Glu111Ala polymorphism of glyoxalase I in patients with breast cancer 36 and were able to show that the higher frequency of the mutated C allele was found in patients with negative estrogen receptors and in patients and more advanced disease (clinical stage III) compared to controls (P < 0.05) suggesting that the presence of the C allele could be a negative prognostic factor in breast cancer. In a large Italian study of patients with breast cancer cancer 37 polymorphism of glyoxalase I was associated with breast cancer in univariate analysis but a number of confounding factors obfuscate the results.…”
Section: Ages Their Metabolism and Cancermentioning
confidence: 99%